(untitled) (Clinics, 2023)
Context: Transtibial Amputation (TA) predisposes to a sedentary lifestyle. Objectives: To evaluate the efficiency of a short-term (8-week) Concurrent Training (CT) program in Unilateral Transtibial Amputees (UTA) and to compare it with the physical condition of a group of Paralympic athletes in preparation for the Rio de Janeiro Paralympics. Design: This was a longitudinal, prospective and controlled trial study. Methods: Thirty-four male subjects with UTA and using prostheses for six months or more were selected for this study. They were divided into two groups: Group 1 (G1) ‒ 17 non-athlete and untrained UTA and Group 2 (G2) ‒ 17 paralympic athletes with active UTA in the training phase. G1 was evaluated before and after eight weeks of CT and G2 made a single evaluation for control. All were submitted to anamnesis, clinical evaluation (blood pressure, electrocardiogram, and heart rate) and cardiopulmonary exercise testing on a lower limb cycle ergometer, and isokinetic knee dynamometry. The CT of G1 included resistance exercise and aerobic interval training on a stationary bicycle and G2 followed the training of the Paralympic teams. Results: Patients were retested by the same methods after CT. The two most important central dependent variables (maximal oxygen uptake and muscular strength) increased by 22% and knee extensor and flexor strength by 106% and 97%, respectively. Conclusion: After eight weeks of CT, there was an improvement in general functional condition, muscle strength, and cardiorespiratory performance improving protection against chronic diseases and quality of life.